Sulfate and phosphate ions removal using novel nano-adsorbents: modeling and optimization, kinetics, isotherm and thermodynamic studies. Issue 14 (6th December 2022) - Shahzadi, Tayyaba; Anwaar, Asma; Riaz, Tauheeda; Zaib, Maria
Abstract: Many compounds containing sulfur and phosphorous are present in wastewater of various industries like food processing, paper making, etc. The higher level of phosphate and sulfate ions causes many problems in everyday life. Based on this, nickel monometallic and nickel-cobalt bimetallic nanoparticles were synthesized using leaves extract of Coix lacryma-jobi L. and applied for sulfate and phosphate ions removal. UV-Vis. spectroscopy, fourier transformed infrared spectroscopy; scanning electron microscopy; X-ray diffraction, and energy-dispersive X-ray spectroscopy were used as characterizing techniques for synthesized nanoparticles. UV spectra for Ni nanoparticles showed the absorption band in the 380–400 nm range, while for Ni-Co bimetallic nanoparticles was noticed at 396 nm and 513 nm. Different functional groups were observed in FTIR spectra of leaves extract which acted as reducing and capping agents to form stable NPs. Different factors like adsorbent dosage, pH, temperature, adsorbate concentration, and time were optimized for maximum removal of sulfate and phosphate anions. The antioxidant potential of prepared nanoparticles was assessed by three different methods. The kinetics, thermodynamics, and adsorption isotherms were also studied for these ions removal. In the current study, the green approach was easy, time-saving and proved to be beneficial to remove sulfate and phosphate anions from wastewater. Novelty statement: The leaves extract of Coix lacryma-jobi L. were employed for the synthesis of nickel monometallic and nickel-cobalt bimetallic nanoparticles and employed for the removal of sulfate and phosphate ions from aqueous solution. Antioxidant potential of biosynthesized nanoparticles was also assessed. Hence, the biosynthesized nanomaterial found to be novel adsorbent for removal of sulfate and phosphate from waste water. This research work has not been previously reported in literature. Graphical Abstract: UF0001